An "AIE+ESIPT" characteristic fluorescent probe for relay recognition of Cu2+ and H2S and its application in food samples and cell imaging. (February 2023) - Pan, Yongxin; Li, Ying; Sun, Xiaofei; Tang, Lijun; Yan, Xiaomei
Abstract: A simple fluorescent probe (TPE-1 ) based on the combination of tetraphenylethene (TPE) and 2-(2′-hydroxyphenyl)benzothiazole (HBT) was synthesized. TPE-1 possesses both aggregation-induced emission (AIE) and excited-state intramolecular proton transfer (ESIPT) characteristics. The TPE-1 aggregates exhibited rapid (10 s) and highly selective recognition of Cu 2+ in THF/H2 O (1:9, v/v, HEPES 20 mM, pH = 7.4) solution, and was induced an "on-off" change in the fluorescence. TPE-1-Cu 2+ complexes generated in situ can also be used as sensing ensembles for highly selective detection of H2 S by Cu 2+ displacement. As a result, the fluorescence of TPE-1 was recovered again, and an "on-off-on" fluorescence variation was used to relay Cu 2+ and H2 S recognition. The detection limits of the probes for Cu 2+ and H2 S are 9.91 × 10 −8  M and 3.80 × 10 −7  M, respectively. In addition, the probes can be applied to detect Cu 2+ and H2 S in some food samples and can also be applied to cell imaging experiments. Graphical abstract: Relay recognition of Cu 2+ and H2 S by a fluorescent probe regulated by AIE and its application in food and cell imaging. Image 1 Highlights: An AIE-based fluorescent probe TPE-1 was designed and synthesized. TPE-1 can relay identify Cu 2+ and H2 S with high sensitivity, high selectivity, large Stokes shift, and low detection limit. TPE-1 can rapidly relay responses to Cu 2+ and H2 S with on-off-on fluorescence changes. TPE-1 is suitable to assay the Cu 2+ and H2 S level in water, seafood, tea and red wine samples.